2015
DOI: 10.1371/journal.pone.0135070
|View full text |Cite
|
Sign up to set email alerts
|

Allergen-Specific Immunotherapy with Monomeric Allergoid in a Mouse Model of Atopic Dermatitis

Abstract: Atopic dermatitis (AD) is a widespread and difficult to treat allergic skin disease and is a tough challenge for healthcare. In this study, we investigated whether allergen-specific immunotherapy (ASIT) with a monomeric allergoid obtained by succinylation of ovalbumin (sOVA) is effective in a mouse model of atopic dermatitis. An experimental model of AD was reproduced by epicutaneous sensitization with ovalbumin (OVA). ASIT was performed with subcutaneous (SC) administration of increasing doses of OVA or sOVA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 39 publications
0
19
0
1
Order By: Relevance
“…Systemic administration of rGal-1 also markedly reduced plasma IL-17A levels compared to the untreated AD group, an important cytokine biomarker for AD patients [20,21]. In a previous mouse model, splenocytes isolated from OVAinduced AD BALB/c mice had significantly increased levels of IL-4, IL-5, IFN-γ and IL-17 after 72 h of OVA stimulation in vitro, whereas unstimulated cells were not significantly different than control animals [22]. Furthermore, in oxazolone-induced AD IL-17-null mice exhibit reduction of skin edema, eosinophilia, IL-4 and IL-13 production in skin and lymph nodes relative to wild-type animals [19,23].…”
Section: Discussionmentioning
confidence: 99%
“…Systemic administration of rGal-1 also markedly reduced plasma IL-17A levels compared to the untreated AD group, an important cytokine biomarker for AD patients [20,21]. In a previous mouse model, splenocytes isolated from OVAinduced AD BALB/c mice had significantly increased levels of IL-4, IL-5, IFN-γ and IL-17 after 72 h of OVA stimulation in vitro, whereas unstimulated cells were not significantly different than control animals [22]. Furthermore, in oxazolone-induced AD IL-17-null mice exhibit reduction of skin edema, eosinophilia, IL-4 and IL-13 production in skin and lymph nodes relative to wild-type animals [19,23].…”
Section: Discussionmentioning
confidence: 99%
“…Increased proportions of Foxp3 + CD4 + Tregs were found in patients treated with immunotherapy [23,24]. Additionally, induction of Tregs in murine models has been postulated to be an essential step in allergen-specific immunotherapy [25][26][27][28]. In 2012, Maazi et al demonstrated that the effects of allergen-specific immunotherapy can be partially explained by Tregs because depletion of Tregs only partially abrogated the suppressive effects induced by the therapy [58].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that kakkonto suppresses the occurrence of allergic symptoms in a murine FA model [21] and kakkonto induces Foxp3 + CD4 + regulatory T cells (Tregs) in the colon as a novel mechanism underlying the therapeutic action [22]. It is reported that allergen-specific immunotherapy increases the production of local and systemic Foxp3 + CD4 + Tregs as an essential step in patients [23,24] and experimental models [25][26][27][28]. Therefore, we hypothesized that kakkonto might have a potential as a therapeutic drug for the treatment of immune diseases induced by the disruption of intestinal mucosal tolerance, such as FAs.…”
Section: Introductionmentioning
confidence: 99%
“…The puried allergen, Art v 1, was modied with cis-aconitic anhydride, which reacts with free amino groups (lysine and free N-terminus) on proteins similar to a reaction with other acid anhydrides, 20 resulting in a monomeric modied protein that is able to bypass mucosal barriers if applied locally. 21 However, cis-aconitylation is a reversible modication due to acyl group hydrolysis under acidic conditions, 8,9,22 and hence during processing in endolysosomal compartments, the allergen completely recovers its native structure.…”
Section: Discussionmentioning
confidence: 99%